Antimicrobial Susceptibility of Neisseria gonorrhoeae Isolates in Baltimore, Maryland, 2016: The Importance of Sentinel Surveillance in the Era of Multi-Drug-Resistant Gonorrhea - Johan H. Melendez; Justin Hardick; Mathilda Barnes; Kathleen R. Page; Charlotte A. Gaydos (MDPI AG, 2018)
The increasing rates of gonorrhea infections and the global emergence and spread of multi-drug-resistant Neisseria gonorrhoeae (NG) threaten the successful management of gonorrhea. In the era of nucleic acid amplification tests (NAATs), surveillance projects are urgently needed to monitor prevalence and trends in the antimicrobial susceptibility of NG. In this study, we retrospectively determined the susceptibility profile of NG isolates to previously and currently prescribed antimicrobials. NG isolates collected in Baltimore, Maryland between January and October 2016 were evaluated by the E-test method and/or molecular methods for susceptibility to ceftriaxone, azithromycin, ciprofloxacin, tetracycline, gentamicin, and penicillin. One-hundred and forty-three NG isolates from African-American males (98.6%), primarily heterosexual (88.8%), ranging in age from 15 to 69 years of age were included in the study. Ciprofloxacin resistance was observed in 44.1% of isolates. Plasmid-mediated resistance to penicillin and tetracycline resistance was detected in 22.4% and 10.1% of isolates, respectively. Three isolates (2.1%) displayed high-level resistance to azithromycin (minimum inhibitory concentration (MIC) > 256 μg/mL). Forty-three percent of isolates were resistant or had decreased susceptibility to three antimicrobials (ciprofloxacin, tetracycline, and penicillin). All isolates were susceptible to ceftriaxone and gentamicin. Overall, the epidemiology of antimicrobial resistant NG in Baltimore continues to evolve, and the emergence of azithromycin resistance in this population emphasizes the need for continued sentinel surveillance programs to monitor susceptibility trends and aid in treatment recommendations.